Impact of distance, exchange rate, population, and GDP on natural rubber export - Raya Yusrizal Saddam Muhammad, Atik Purmiyati, (Opción, 2020)
The study aims to investigate the impact of distance, exchange rate, population, and GDP on natural rubber export. This study utilized two approaches, namely a descriptive approach and a quantitative approach, and used the gravity model approach in the process because the research used distance as one of the reference variables. As a result, a high GDP indicated higher income, and high income would lead to an increase in disposable income. In conclusion, the government should try to keep the rupiah exchange rate stable or even to increase it to maintain the stability of the Indonesian natural rubber trade flow.